A review of approaches to low-carbon transition of high-rise residential buildings in China. (October 2020) - Wang, Y.; Mauree, D.; Sun, Q.; Lin, H.; Scartezzini, J.L.; Wennersten, R.
Abstract: In developing countries with a large population and fast urbanization, High-rise Residential Buildings (HRBs) have unavoidably become a very common, if not the most, accommodation solution. The paradigm of HRB energy consumption is characterized by high-density energy consumption, severe peak effects and a limited site area for integrating renewable energy, which constitute a hindrance to the low-carbon transition. This review paper investigates low-carbon transition efforts in the HRB sector from the perspective of urban energy systems to get a holistic view of their approaches. The HRB sector plays a significant role in reducing carbon emission and improving the resilience of urban energy systems. Different approaches to an HRB low-carbon transition are investigated and a brief overview of potential solutions is offered from the perspectives of improving energy efficiency, self-sufficiency and system resilience. The trends of decarbonization, decentralization and digitalization in the HRB sector allow a better alignment with transitioning urban energy systems and create cross-sectoral integration opportunities for low-carbon transition. It is also found that policy tools are powerful driving forces in China for incentivizing transition behaviors among utilities, end users and developers. Based on a comprehensive policy review, the policy implications are given. The research is geared for the situation in China but could also be used as an example for other developing countries that have similar urbanization patterns. Future research should focus on quantitative analysis, life-cycle analysis and transdisciplinary planning approaches. Highlights: The role, approaches and impacts of low-carbon transition efforts in the HRB sector. Interactive relationship between the HRB sector and urban energy systems. Trends of decarbonization, decentralization and digitalization in the HRB sector. Realistic low-carbon transition solutions for HRBs in China. Policy implications for inherent planning of HRBs and urban energy systems.